The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1016/j.pss.2019.104748
|View full text |Cite
|
Sign up to set email alerts
|

Proving the viability of an electrochemical process for the simultaneous extraction of oxygen and production of metal alloys from lunar regolith

Abstract: The development of an efficient process to simultaneously extract oxygen and metals from lunar regolith by way of in-situ resource utilisation (ISRU) has the potential to enable sustainable activities beyond Earth. The Metalysis-FFC (Fray, Farthing, Chen) process has recently been proven for the industrial-scale production of metals and alloys, leading to the present investigation into the potential application of this process to regolith-like 2 materials. This paper provides a proof-of-concept for the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(40 citation statements)
references
References 31 publications
(32 reference statements)
2
32
0
Order By: Relevance
“…This condition is in contrast to that of the electro-reduction of TiO 2 , whose perovskitization results in the increased volume of the solid phase and hence blockage of the pores in the oxide cathode, impeding the removal of O 2− and the whole electrolysis. Continuous CaTiO 3 electrolysis via Reaction (16) will lead to the accumulation of CaO in the molten salt. However, one can in principle combine Reactions ( 16) and ( 13) to form a closed loop in which CaO is cycled and functions like a "phase change catalyst" to accelerate the electrolysis of TiO 2 .…”
Section: Perovskitization Of Metal Oxides On Cathodementioning
confidence: 99%
See 1 more Smart Citation
“…This condition is in contrast to that of the electro-reduction of TiO 2 , whose perovskitization results in the increased volume of the solid phase and hence blockage of the pores in the oxide cathode, impeding the removal of O 2− and the whole electrolysis. Continuous CaTiO 3 electrolysis via Reaction (16) will lead to the accumulation of CaO in the molten salt. However, one can in principle combine Reactions ( 16) and ( 13) to form a closed loop in which CaO is cycled and functions like a "phase change catalyst" to accelerate the electrolysis of TiO 2 .…”
Section: Perovskitization Of Metal Oxides On Cathodementioning
confidence: 99%
“…In the past two decades, world-wide research and development have confirmed the scientific principle and technical feasibility and flexibility of the process for the extraction of almost all metals listed in the periodic table and their alloys from their respective oxide or sulfide precursors [6][7][8][9][10][11][12][13][14]. In addition, the FFC Cambridge Process has versatile applications in other fundamental and industrial areas, such as near-net shape manufacturing of metallic artifacts of complex structures, medical implants, oxygen generation on the moon, capture and electrolytic conversion of carbon dioxide (CO 2 ) to various forms of carbon, e.g., carbon nanotubes, carbon monoxide (CO), and hydrocarbon fuels (C n H 2n+2 , n < 10), and rechargeable molten salt metal-air batteries [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The process has since been shown to be capable of reducing many different metal oxides, including those of tantalum, chromium and cerium [2][3][4]. Mixed-metal oxides can also be reduced simultaneously, allowing for the direct production of alloys, as well as more novel materials like high-entropy alloys and those derived from lunar regolith simulant material [5][6][7][8][9].…”
Section: Ti Extraction Via the Ffc-cambridge Processmentioning
confidence: 99%
“…As shown recently [15], the so-called FFC Cambridge electrolytic process can be used to separate earthly, lunar or asteroid rock into oxygen gas and a solid residue comprising metals and silicon. The oxygen can be used as Electric Propulsion propellant [16].…”
Section: Asteroid Materials Transferred By O 2 Electric Propulsionmentioning
confidence: 99%